Aspek Tatalaksana Pemberian Pakan Pada Usaha Peternakan Babi Rakyat; Kasus Di Wilayah Pesisir Pantai Manokwari Papua - Pattiselanno, Freddy; Randa, Sangle Yohanes (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2006)
A study to identifY the possibility on the development of swine raising managed traditionally by local communities on the coastal area of Manokwari district was conducted in Manokwari district (Kecamatan Manokwari; Kelurahan Manokwari Barat and Kelurahan Manokwri Timur). Data collection was carried out through field survey, observation and interviewing 35 respondent farmers Who have been raising swine for at least a year. For the future development, the requirements of good feeding management, feed additive (vitamin and mineral) is urgently to be applied with regards to enrich feed nutrients for the animals. Feed nutrition analysis of the consumed feeding is important to do serve as the base line information for the feeding management requirements. Feed availability was showed by various feed items, feeding sources diversity, and common practice of feeding frequency that appropriate as requirements for raising swine.